Cercetări privind stabilirea termenelor de valabilitate a prunelor uscate umplute cu miez de nucă [Articol] - Şleagun, Galina (USARB, 2017)
This paper presents the results of the quality study during shelf life of a diverse assortment of dried prunes filled with walnut kernel. Product quality was assessed with oxidation indices (peroxide and thiobarbituric number) and organoleptic characteristics. Shelf life period was predicted using the method of shelf life accelerated determination for drugs. There was established that tested product keep its good quality for more than 9 months. Vacuum packaging prevents the oxidation process and can significantly increase the shelf life. The optimal product moisture was found as 25-27%.
Keywords: dried prunes; walnut kernel; validity period; oxidation indices; peroxide number; thiobarbituric number